Provider Differences in Use of Implanted Ports in Older Adults With Cancer. Issue 7 (July 2015) - Lipitz-Snyderman, Allison; Elkin, Elena B.; Atoria, Coral L.; Sima, Camelia S.; Epstein, Andrew S.; Blinder, Victoria; Sepkowitz, Kent A.; Bach, Peter B.
Abstract : Background: Identifying unwarranted variation in health care can highlight opportunities to reduce harm. One often discretionary process in oncology is use of implanted ports to administer intravenous chemotherapy. While there are benefits, ports carry risks. This study's objective was to assess provider-driven variation in port use among cancer patients receiving chemotherapy. Research Design: Retrospective assessment using population-based SEER-Medicare data to assess differences in port use across health care providers of older adults with cancer. Participants included over 18, 000 patients ages 66 and older diagnosed with breast, colorectal, lung, or pancreatic cancer in 2005–2007, treated by approximately 2900 providers. We identified port use for patients receiving treatment from hospital outpatient facilities versus physicians' offices. Our main analysis assessed the likelihood of a patient receiving a port given port use by the provider's last patient. For a subset of high-use providers, we examined individual provider-level variation by estimating the risk-adjusted likelihood of insertion. Results: Patients receiving chemotherapy in hospital outpatient facilities were significantly less likely to receive a port than those treated in physicians' offices, with adjusted odds ratios (AOR) varying from 0.50 to 0.75 across cancer sites. Implanting a port was associated with increased likelihood of port insertion in the provider's next patient (AOR varied from 1.71 to 2.25). Significant between-provider variation was found among providers with at least 10 patients. Conclusions: Our findings support the idea that there is provider-driven variation in the use of ports for chemotherapy administration. This variation highlights an opportunity to standardize practice and reduce unnecessary use. Abstract : Supplemental Digital Content is available in the text.